DISIPLIN GURU DALAM PEMBELAJARAN - Muai Muai (Manajer Pendididikan, 2015)
The objective of this study was describe teacher discipline in learning in Junior High School number two in Lubuklinggau City, South Sumatra Province. The qualitative descriptivemethod was used in this study. The subject of this study was principal, teachers, and students. Data was collected through interviews, observation, and documentations. Data analysis included data collection, reductioning data, display the data. At last the researcher can conclude that the teacher discipline in planning in learning, the teacher discipline actuating in learning, and the teacher discipline evaluating in learning have been done in junior high school number two in Lubuklinggau City, South Sumatera Province.Keyword: teacher, discipline, learning